Implementation and application of automata : 21st International Conference, Proceedings, CIAA 2016, Seoul, South Korea, July 19-22, 2016. Proceedings /: 21st International Conference, Proceedings, CIAA 2016, Seoul, South Korea, July 19-22, 2016. Proceedings. ([2016]) - Unknown
No abstract available